Inflammasome activation during spontaneous preterm labor with intra‐amniotic infection or sterile intra‐amniotic inflammation. (18th September 2018) - Gomez‐Lopez, Nardhy; Romero, Roberto; Panaitescu, Bogdan; Leng, Yaozhu; Xu, Yi; Tarca, Adi L.; Faro, Jonathan; Pacora, Percy; Hassan, Sonia S.; Hsu, Chaur‐Dong
Abstract : Problem: The inflammasome is implicated in the mechanisms that lead to spontaneous preterm labor (PTL). However, whether there is inflammasome activation in the amniotic cavity of women with PTL and intra‐amniotic infection (IAI) or sterile intra‐amniotic inflammation (SIAI) is unknown. Method of study: Amniotic fluid samples were collected from women with PTL who delivered at term (n = 31) or preterm without IAI or SIAI (n = 35), with SIAI (n = 27), or with IAI (n = 17). As a readout of inflammasome activation, extracellular ASC (apoptosis‐associated speck‐like protein containing a CARD) was measured in amniotic fluid by ELISA and the expression of ASC, caspase‐1, and interleukin (IL)‐1β was detected in the chorioamniotic membranes by multiplex immunofluorescence. Acute inflammatory responses in amniotic fluid and the placenta were also evaluated. Results: (a) Amniotic fluid concentrations of ASC and IL‐6 were higher in women with PTL and IAI or SIAI than in those who delivered preterm or at term without intra‐amniotic inflammation; (b) amniotic fluid concentrations of ASC and IL‐6 were lower in women with PTL and SIAI than in those with IAI; (c) there was a significant nonlinear correlation between ASC and IL‐6 amniotic fluid concentrations; (d) the expression of inflammasome‐related proteins (ASC, caspase‐1, and IL‐1β) in the chorioamniotic membranes was increased in women with PTL and IAI or SIAI than in those who delivered preterm or at term without intra‐amniotic inflammation; (e) inflammasome activation in the chorioamniotic membranes was weaker in women with PTL and SIAI than in those with IAI; (f) women with PTL and IAI had elevated amniotic fluid white blood cell counts compared to those without this clinical condition; and (g) severe acute placental inflammatory lesions were observed in women with PTL and IAI and in a subset of women with PTL and SIAI. Conclusion: Inflammasome activation occurs in the settings of intra‐amniotic infection and sterile intra‐amniotic inflammation during spontaneous preterm labor.